Ethical responsibility in the SBBrasil 2010 from the perspective of the managers of the population survey - Andrade, Flavia Reis de; Narvai, Paulo Capel; Montagner, Miguel Angelo (Revista de Saúde Pública, 2013)
OBJECTIVE: To analyze the ethical problems involved in the Brazilian Oral Health Survey – SBBrasil 2010. METHODS: We carried out a descriptive qualitative case study from the perspective of the ethics of responsibility. Key informants (n = 14) involved in the planning and implementation of a population survey in the Federal District and 11 States were individually interviewed using a semi-structured questionnaire. The participants of this research belonged either to the Management Group or the Technical Advisory Committee of the Ministry of Health, responsible for the planning and implementation of SBBrasil 2010. Two coordinators, one municipal the other state were also involved. The results are expressed as collective subject discourse. Complementary information about the content of the interviews was obtained from the participants in order to clarify terms and to understand facts and contexts. RESULTS: The following core ideas were identified: the teams need to feel responsible for SBBrasil 2010; fabrication of data compromised the DMFT (decayed, missing, filled tooth) in some places; non-adherence to field work protocol as moral problem. Data exam showed that in one capital the caries index at 12 years was well above the average expected for that place. A breakdown of the database led to the detection of solid evidence of registration error on the part of two examiners, which would indicate that there was either a failure in the training and calibration stage, or fabrication of data, or both. CONCLUSIONS: The anomalous behavior of these examiners was detected in time and the fieldwork was redone. However, from the perspective of the ethics of responsibility, there was a transgression in the sphere of individual responsibility, the effects of which affected all the researchers involved and jeopardized the credibility of the research.